Sulfurization of Electrodeposited Sb/Cu Precursors for CuSbS2: Potential Absorber Materials for Thin-Film Solar Cells - Zhao, Aimei; Wang, Yanping; Li, Bing; Xiang, Dongmei; Peng, Zhuo; Yuan, Yujie; Xing, Yupeng; Yao, Liyong; Bi, Jinlian; Li, Wei (Frontiers in Materials, 2022)
CuSbS2, as a direct bandgap semiconductor, is a promising candidate for fabricating flexible thin-film solar cells due to its low grain growth temperature (300°C–450°C). Uniform and highly crystalline CuSbS2 films are crucial to improve device performance. However, uniform CuSbS2 is difficult to obtain during electrodeposition and post-sulfurization due to the “dendritic” deposition of Cu on Mo substrates. In this study, Sb/Cu layers were sequentially pulse electrodeposited on Mo substrates. By adjusting the pulse parameters, smooth and uniform Sb layers were prepared on Mo, and a flat Cu layer was obtained on Sb without any dendritic clusters. A two-step annealing process was employed to fabricate CuSbS2 films. The effects of temperature on phases and morphologies were investigated. A CuSbS2 thin film with good crystallinity was obtained at 360°C. As the annealing temperature increased, the crystallinity of the films decreased. The CuSbS2 phase transformed into a Cu3SbS4 phase with the temperature increase to 400°C. Finally, a 0.90% efficient solar cell was obtained using the CuSbS2 film annealed at 360°C.